2014
DOI: 10.15252/embj.201488837
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale segregation of actin nucleation and elongation factors determines dendritic spine protrusion

Abstract: Actin dynamics drive morphological remodeling of neuronal dendritic spines and changes in synaptic transmission. Yet, the spatiotemporal coordination of actin regulators in spines is unknown. Using single protein tracking and super-resolution imaging, we revealed the nanoscale organization and dynamics of branched F-actin regulators in spines. Branched F-actin nucleation occurs at the PSD vicinity, while elongation occurs at the tip of finger-like protrusions. This spatial segregation differs from lamellipodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
129
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 106 publications
(230 reference statements)
12
129
0
2
Order By: Relevance
“…In contrast to the branched actin created by the Arp2/3 complex, formins facilitate the polymerization of linear actin filaments. Recent super-resolution imaging reveals that spines are not smooth bulbous structures, as they often appear in conventional light microscopy, but rather they contain fine, finger-like projections from the spine head (18) (Fig. 1).…”
Section: Dendritic Spine Actin Regulatorsmentioning
confidence: 99%
“…In contrast to the branched actin created by the Arp2/3 complex, formins facilitate the polymerization of linear actin filaments. Recent super-resolution imaging reveals that spines are not smooth bulbous structures, as they often appear in conventional light microscopy, but rather they contain fine, finger-like projections from the spine head (18) (Fig. 1).…”
Section: Dendritic Spine Actin Regulatorsmentioning
confidence: 99%
“…Tatavarty et al also showed a dominating population of unpolarized actin foci within spine heads and necks. Further complicating the picture, a recent study by Chazeau et al (120) reported no polarized actin flow within the spines, but localized actin protrusions at the perisynaptic region. This variation in experimental observations may suggest temporal heterogeneity, in the sense that polarized actin flow only appears transiently and may be regulated by the environment.…”
Section: Spine Polaritymentioning
confidence: 99%
“…Interestingly, most experimental results indicate that the real dynamics are significantly more complex. For example, several labs have investigated filamentous actin movement within dendritic spines using sptPALM (118)(119)(120). Results from Frost et al (118) show convincing evidence for slow but polarized actin flow within dendritic spines.…”
Section: Spine Polaritymentioning
confidence: 99%
“…First, Grégory Giannone (Interdisciplinary Institute for NeuroScience, Bordeaux, France) presented the use of single-particle tracking (spt) combined with photoactivated localisation microscopy (PALM) -so called sptPALM -and super-resolution microscopy to study the displacement of integrins and their relative distribution between the outside and inside of mature focal adhesions (Rossier et al, 2012). He also applied the same approach to study the dynamic organization of F-actin regulators in neuronal dendritic spines (Chazeau et al, 2014). On the basis of his data, he suggested spatial segregation of specific protein interactions into distinct nanodomains to be a general mechanism in order to locally regulate protein activity within sub-cellular structures.…”
Section: Super-resolution Imagingmentioning
confidence: 99%